Insights into the molecular phylogeny and morphology of three novel Dothiora species, along with a worldwide checklist of Dothiora - Senwanna, Chanokned; Hongsanan, Sinang; Khuna, Surapong; Kumla, Jaturong; Yarasheva, Manzura; Gafforov, Yusufjon; Abdurazakov, Aziz; Suwannarach, Nakarin (Frontiers in Cellular and Infection Microbiology, 2024)
Most species of Dothiora are known from the dead parts of various host plants as saprobic fungi in terrestrial habitats occurring in tropical and temperate regions. In the present study, samples of Dothiora were collected from dead twigs and branches of Capparis spinosa, Rhaponticum repens, and an unknown angiosperm plant from the Tashkent and Jizzakh regions of Uzbekistan. Multigene phylogenetic analyses based on a combined ITS, LSU, SSU, TEF1, and TUB2 sequence data, revealed their taxonomic positions within the Dothideaceae. Three new species of Dothiora, namely D. capparis, D. rhapontici, and D. uzbekistanica were proposed by molecular and morphological data. Likewise, the phylogenetic relationship and morphology of Dothiora are discussed. In addition, we provide a list of accepted Dothiora species, including host information, distribution, morphology descriptions, and availability of sequence data, to enhance the current knowledge of the diversity within Dothiora.